Non-Inguinal Ventral Hernias: An Updated Review for Healthcare Providers - Alshibl , Ibrahim Yahya Ibrahim; Aldosri, Wadha Faleh; Alshamrani, Ali Abdullah; Alhesham, Sultan Mohammed Sorror; Al Otaibi, Nomas Saqer; Alotaibi, Mansour Bijad; Qarradi, Fatimh Hassan; Alghamdi, Sami Hussain; Haddadi , Abdullah Musawa; Mutanbak, Taha Hussein; Alshehri , Rawabi Mohammed Ali; Aldawsari, Alaa Mohammed Abdulaziz; et al. (Journal of Ecohumanism, 2024)
Background: Ventral hernias, defined as non-inguinal and nonhiatal fascial defects in the abdominal wall, are a significant clinical concern, with approximately 350,000 repairs performed annually in the United States. These hernias can impair quality of life, lead to hospitalizations, and, in severe cases, result in mortality. The etiology includes congenital and acquired factors, with obesity, prior surgeries, and repetitive abdominal stress being major contributors. Surgical repair is the primary treatment, but recurrence and complications remain challenges. Aim: This review aims to provide an updated overview of the etiology, epidemiology, pathophysiology, diagnosis, and management of ventral hernias, emphasizing evidence-based strategies to improve outcomes and reduce complications. Also, the study focus on the critical role of anesthesiologists in the ventral hernia surgery and post-operative management. Methods: The review synthesizes current literature on ventral hernias, including classification systems, diagnostic approaches, surgical techniques, and postoperative care. It highlights the role of imaging, preoperative optimization, and the use of synthetic versus biologic meshes. The review also discusses the importance of multidisciplinary collaboration and patient education in enhancing outcomes. Results: Ventral hernia repair outcomes vary based on surgical technique, patient factors, and hernia characteristics. Laparoscopic and robotic-assisted repairs are associated with lower recurrence rates and faster recovery compared to open techniques. Mesh use significantly reduces recurrence, but infection remains a catastrophic complication. Component separation techniques, such as transversus abdominis release (TAR), are effective for large hernias but are technically demanding. Parastomal hernias require specialized repair techniques, with prophylactic mesh placement reducing incidence. Conclusion: Ventral hernias are a complex surgical challenge requiring tailored approaches based on patient and hernia-specific factors. Advances in surgical techniques, mesh technology, and multidisciplinary care have improved outcomes, but recurrence and complications remain significant concerns. Continued research and adherence to evidence-based practices are essential to further enhance patient outcomes.